Religija, digitalni mediji in epidemija covida-19 - Moberg, Marcus (Poligrafi, 2024)
This introductory paper to the thematic strand on religion and digital techno-logies during and following the COVID-19 pandemic begins with a brief outline of how primarily Christian and Islamic religious communities are grappling with rapidly developing digital technologies. A synoptic description of research deve-lopments in the relatively new field of religion and digital media follows, drawing on an overview of basic readings and research, with a particular focus on the surge in ICT use during 2020 and 2021 as a result of the global pandemic. The paper concludes with a brief presentation of the international research project Religious Communities in the Virtual Age, on which this thematic strand is based.
Keywords: Covid-19; digitalni mediji; Religija